1993
DOI: 10.1148/radiology.187.1.8451412
|View full text |Cite
|
Sign up to set email alerts
|

Role of SPECT in differentiating malignant from benign lesions in the lower thoracic and lumbar vertebrae.

Abstract: The authors categorized 125 spinal lesions in cancer patients and 127 lesions in patients with back pain according to their location in the vertebra on single photon emission computed tomographic (SPECT) images. Forty-four lesions were metastases, all in patients with known malignancy. Lesions in the apophyseal joints were all benign. Lesions manifesting as abnormal uptake projecting beyond the vertebral body surface were osteophytes. Thirty-seven percent of the lesions detected in cancer patients were categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(51 citation statements)
references
References 0 publications
3
48
0
Order By: Relevance
“…Atypical patterns of uptake and coexisting benign bone pathologies present a challenge in differentiating benign from malignant disease with planar bone scintigraphy alone. Several studies have reported improved diagnostic accuracy with the addition of SPECT, particularly in the vertebral column through improved tracer localisation [20][21][22]. As a general rule, uptake in the vertebral body or the pedicle alone is more likely to represent malignant disease than a pattern of uptake isolated to the vertebral body periphery or at the facet joints [23,24].…”
Section: Applications In Musculoskeletal Radiologymentioning
confidence: 99%
“…Atypical patterns of uptake and coexisting benign bone pathologies present a challenge in differentiating benign from malignant disease with planar bone scintigraphy alone. Several studies have reported improved diagnostic accuracy with the addition of SPECT, particularly in the vertebral column through improved tracer localisation [20][21][22]. As a general rule, uptake in the vertebral body or the pedicle alone is more likely to represent malignant disease than a pattern of uptake isolated to the vertebral body periphery or at the facet joints [23,24].…”
Section: Applications In Musculoskeletal Radiologymentioning
confidence: 99%
“…According to the diagnostic method described by Even-Sapir et al (11), the results of the bone scans were interpreted as metastatic bone lesions under these circumstances: i) Vertebral lesions of increased uptake involved the posterior aspect of the vertebral body and pedicle, or involved the vertebrae extensively (12,13); ii) rib lesions of increased uptake exhibited the strip form (14); iii) the lesions of increased uptake exhibited the lamellar form with or without corroding multiple adjacent bones (14); iv) the lesions of decreased uptake were confirmed to not be bone cysts and ischemic bone necrosis, or accompanied progressive osteodynia symptoms; v) the lesions of markedly increased uptake were confirmed to not be benign bone diseases, or exhibited multiple sites and scrambled arrangement; vi) the bone lesions, of increased or decreased uptake, were confirmed to be bone metastases by X-ray, CT or MRI; vii) by comparing the result of bone scans that were performed at different times, the new bone lesions could not be interpreted as benign diseases, or the lesions presented 'flare phenomenon' (15). The results of bone scans were considered negative under the following circumstances: i) no abnormal radiotracer uptake was detected; ii) there was indeterminate decreased radioactivity in local bones; iii) the bone lesions of increased or decreased radiotracer uptake were characterized as benign disease.…”
Section: Diagnostic Criteria Of Bone Metastasis the Interpretations mentioning
confidence: 99%
“…This increased software complexity was partially accomplished by means of incorporation of newer techniques for 2D candidate merging, as well as by means of SVM classifier training on 3D features (compared with 2D SVM feature training, performed in the prior lytic lesion work). Ten patients without sclerotic spinal metastases were used in the software training and testing phases of this work spread to the vertebrae are in the vertebral body and pedicles, and most of the volume of each vertebra is constituted by these regions (38)(39)(40). Bounding box inclusion of the vertebral body and pedicles thus assesses the most likely regions of early metastatic tumor involvement.…”
Section: Discussionmentioning
confidence: 99%